2015
DOI: 10.1001/jamasurg.2015.1683
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Bilateral Adrenal Incidentalomas and Unilateral Lesions

Abstract: Bilateral incidentalomas are more likely to be associated with subclinical Cushing syndrome and less likely to be pheochromocytomas. Although patients with bilateral incidentalomas undergo a workup similar to that in patients with unilateral lesions, differences in their natural history warrant a greater index of suspicion for subclinical Cushing syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
9
18
2
Order By: Relevance
“…Moreover, we found that patients with primary aldosteronism were more likely to present a lesion in the contralateral gland than participants without this disorder. Accumulating data suggest that adrenal incidentalomas are unilateral in more than 80% of cases, similar to our results. Regarding the lateralization of adrenal incidentalomas among individuals with primary aldosteronism, existing data are quite restricted.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we found that patients with primary aldosteronism were more likely to present a lesion in the contralateral gland than participants without this disorder. Accumulating data suggest that adrenal incidentalomas are unilateral in more than 80% of cases, similar to our results. Regarding the lateralization of adrenal incidentalomas among individuals with primary aldosteronism, existing data are quite restricted.…”
Section: Discussionsupporting
confidence: 92%
“…However, hypertension, diabetes type 2 and dyslipidemia were comparable in both groups (65). More recently, in a surgical series including 112 unilateral AI and 23 bilateral AI, mild cortisol excess was present in 21.7% bilateral AI vs 6.2% of unilateral AI (66). Vassiliadi et al demonstrated an exaggerated response of cortisol and ACTH in patients with bilateral AI during the combined test of DST followed by CRH stimulation compared to unilateral AI and to a control group suggesting that the regulation of hypothalamicpituitary axis was disturbed in patients with bilateral AI; nevertheless, the diagnosis of BMAH was not excluded in this group (67).…”
Section: Modest Secretion Of Cortisol Is More Frequent In Bilateral Amentioning
confidence: 88%
“…Bilateral masses have been observed from 9.4-20% (Kasperlik-Zaluska et al 2010;Tabuchi et al 2015). Bilateral incidentalomas are more likely associated with subclinical Cushing syndrome and less likely with the pheochromocytoma (Pasternak et al 2015). Th e average diameter of tumors was 21±11mm (Paterson et al 2014;Tabuchi et al 2015).…”
mentioning
confidence: 99%